The Protective Effects of Microbe Derived Antioxidants on Digestive Tissue Morphology, Functions, and Intestinal Microbiota Diversity of Eriocheir sinensis Exposed to Glyphosate - Yameng Song; Mengyao Wu; Yongxu Cheng; Chao Niu; Xiaowen Yu; Yangyang Pang; Xiaozhen Yang (Aquaculture Nutrition)
Conclusion: Gly has certain effects on the digestive tissue function, intestinal microbial diversity index and intestinal microbiota structure of E. sinensis, and MA can ameliorate the negative effects of Gly on E. sinensis.